VISUAL EXPRESSION OF THE LOTUS FLOWER PHILOSOPHY IN PAINTING ARTWORKS - Prayoga, I Made; Budiaprilliana, Luh; Budiarta, I Dewa Putu Gede (Program Studi Seni Murni ISI Bali, 2025)
This report explains the creation of a painting with the theme